No Evidence of Within-Domain Moral Licensing in the Environmental Domain - Urban, Jan; Braun Kohlová, Markéta; Bahník, Štěpán (Environment and behavior, 2021)
Several studies have suggested that people might be less likely to engage in proenvironmental behavior subsequent to their prior engagement in proenvironmental behavior. We have conducted a preregistered replication of one such recent study of within-domain licensing in the area of environmental protection. Our replication was extended with an analysis of self-perception as a potential mediator of licensing and environmental attitude as its moderator. The results of our web-based experiment (N = 1,765) show that recollection of past proenvironmental behavior does not diminish subsequent support of a proenvironmental energy policy or proenvironmental intention, and that environmental attitude does not moderate licensing. We only found some evidence of an indirect effect of recollection on subsequent policy support and proenvironmental intention, mediated by self-perception; the pattern of mediation is, however, inconsistent with the licensing theory. We have not replicated the licensing effect observed in the original study.